Oscillating expression of interleukin-16 in multiple myeloma is associated with proliferation, clonogenic growth, and PI3K/NFKB/MAPK activation - Templin, Julia (Oncotarget, 2017)
Multiple myeloma (MM) is an incurable hematologic malignancy emerging from a plasma cell clone located in the bone marrow and is characterized by a high rate of fatal relapses after initially effective treatment. We have previously identified Interleukin-16 (IL-16) as an important factor promoting the proliferation of MM cells. We demonstrate here an upregulated, periodic expression, and secretion of IL-16 by MM cells leading to high extracellular IL-16 levels. The level of IL-16 released from a given MM cell line correlated with its proliferative activity. Establishing an inducible knockdown system and performing gene expression arrays we observed an association between IL-16 expression and activation of PI3, NFκB and MAP kinase pathways and, specifically, genes involved in tumor cell proliferation. Functional assays showed that IL-16 knockdown reduced the proliferative activity with a significant delay in cell cycle progression to G2 phase of conventional MM cells and completely suppressed the growth of clonogenic MM cells, which are suspected to be responsible for the high relapse rates in MM. Overall, our results demonstrate that tumor-regenerating MM cells may be particularly susceptible to IL-16 neutralization, suggesting an important role of anti-IL-16 therapies in the treatment of MM, particularly in combination with existing strategies targeting the bulk of myeloma cells.